2006
DOI: 10.1385/bter:112:3:205
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc in Patients with Cystic Fibrosis at Diagnosis and After One Year of Therapy

Abstract: There is no consensus whether zinc (Zn) supplementation is necessary in cystic fibrosis (CF). For assessment of the Zn status, serum Zn concentration is the only easy available method. It is, however age dependent. We compare the serum Zn levels of CF patients with earlier reported normal values. Serum Zn was determined in all new diagnosed CF patients and a second time 1 yr later. Data concerning fat-soluble vitamin status, cholesterol, albumin, pancreatic insufficiency, and genotype were collected. Thirty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Several studies evaluating the Zn status of CF patients were based on serum Zn concentrations. The results, however, are contradictory [3][4][5][6][7] . Since symptoms of Zn deficiency are nonspecific and overlap those of CF, detection of clinical deficiency is difficult.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies evaluating the Zn status of CF patients were based on serum Zn concentrations. The results, however, are contradictory [3][4][5][6][7] . Since symptoms of Zn deficiency are nonspecific and overlap those of CF, detection of clinical deficiency is difficult.…”
Section: Introductionmentioning
confidence: 98%
“…Earlier we reported the results of a cross-sectional examination of our CF population [4,16] . Among them we identified a cohort of severely affected children, presenting severe pancreatic insufficiency, loss of appetite, low nutritional intake and stunted growth combined with low serum Zn values [4,16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous contribution newly diagnosed, untreated CF patients were compared to healthy age-matched controls and no differences of serum Zn concentrations were observed in CF as well at diagnosis, as after one year of CF therapy (9). Since many of the older CF patients still present symptoms also commonly seen in Zn deficiency, a cross-sectional study of the serum Zn concentration of treated CF patients was performed here.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that steatorrhea causes loss of zinc in the stool and should lead to low zinc levels among children with cystic fibrosis. However, no such relation was found in the study on 36 children with cystic fibrosis by Van Biervliet et al 14 Another study reported that serum zinc levels in children with cystic fibrosis were similar to those of normal controls but that children with lower serum zinc levels had significantly worse results on the pulmonary function tests. 15 An increase has been observed in the sputum zinc levels in pulmonary exacerbations, and a decrease has been observed in the levels after treatment in bronchiectasis (cystic fibrosis and non-cystic fibrosis bron- chiectasis); however, the significance of this remains unclear.…”
Section: Discussionmentioning
confidence: 90%